H2 receptor antagonists and prokinetics in dyspepsia: a critical review. (1st May 2002) - Bytzer, P
Abstract : Drug treatment of patients with functional dyspepsia is controversial but H2 receptor antagonists have been the mainstay of treatment. For patients with symptoms suggestive of dysmotility, prokinetics such as cisapride have been used. A large number of clinical trials have been unable to produce definite answers as to whether any of these treatment modalities are truly efficacious. This is partly due to the fact that the methodology and reporting of the majority of trials evaluating the symptomatic effects of H2 receptor antagonists and cisapride are severely flawed. Based on the current literature, H2 receptor antagonists may possibly have a therapeutic gain of approximately 20% over placebo. Evaluating the therapeutic gain of cisapride is more difficult but meta-analyses indicate a somewhat larger effect.